Pemanfaatan Sosial Media Branding pada Mitra Anugrah Jaya untuk Meningkatkan Pemasaran Digital Aneka Keripik Extra Delicious - Weda Adistianaya Dewa; Indah Dwi Mumpuni; Linda Suvi` Rahmawati (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2022)
Social media is the right medium for marketing, developing content, posting products, asking for input, and others that can improve and keep their business from losing out in the midst of the existing competition. One of the business industries that will develop is Anugrah Jaya’s partner which is engaged in the food processing industry, namely Assorted Chips